Tingkat Kecerahan Sisik Bagian Pangkal Caput, Dorsal dan Pangkal Caudal Ikan Barbodes lateristriga yang Ditemukan di Sungai Mentuka Kabupaten Sekadau - Tri Rima Setyawati, Mia Audina, Ari Hepi Yanti (Universitas Tanjungpura, 2017)
Barbodes lateristriga is one of the Cyprinidae Family which has a unique colour scales with different colour intensity in some parts of the body. The aim of this study is to know the brightness level of scale of B. lateristriga which found in Mentuka River. This study was conducted three months from November 2016 to January 2017 in Mentuka River at Pantok, Nanga Taman District, Sekadau Regency. Sample taken by using fishing net, landing net, and posat. Fish sample obtained measured the brightness level of scale at the base of caput, dorsal, and the base of caudal by using modified and scaled Trumatch Colour. The result showed that B. lateristriga had higher brightness level of scales at the base of caput and dorsal is 10 meanwhile brightness level of scale at the base of caudal is 1. Mentuka River is still in good condition to support the life of fish and natural food that exist with the temperature 26-28ÂºC, depth and brightness level between 32-89 cm and also has high DO level >6 mg/L.